Strategi pemasaran dalam menggunakan media sosial Instagram pada toko Ciasem Sport16 - Ramadhan, Aditya; Adhim, Muhammad Rizki Faudzil; Sandi, Santi Pertiwi Hari; Hidayanty, Dwi Epty (Relawan Sosial Ekonomi (RSE) Publisher, 2023)
The purpose of this study was to determine marketing strategies using social media Instagram at the Ciasem Sport16 Subang Store with regard to product, price, promotion and location. Method using qualitative research with this type of research descriptive approach used is a case study for this research using source triangulation techniques and method triangulation. The results of this study indicate that using the Instagram marketing strategy prioritizes product quality in its product range so that it can produce high-quality sports equipment, the price combination (price) is carried out at the Ciasem Sport16 Subang Shop.